NF‐κB Activity in Perinatal Brain During Infectious and Hypoxic‐Ischemic Insults Revealed by a Reporter Mouse - Kielland, Anders (Brain Pathol, 2011)
Infants suffering from infection or hypoxia–ischemia around the time of birth can develop brain damage resulting in life‐long impairment such as cerebral palsy, epilepsy and cognitive disability. Inflammation appears to be an important contributor irrespective of whether the primary event is infection or hypoxia–ischemia. Activation of the transcription factor NF‐κB is a hallmark of inflammation. To study perinatal brain inflammation, we developed a transgenic reporter mouse for imaging NF‐κB activity in live animals and tissue samples. The reporter genes firefly luciferase and a destabilized version of enhanced GFP (dEGFP) were regulated by common NF‐κB sites using a bidirectional promoter. Luciferase activity was imaged in vivo, while dEGFP was detected at cellular level in tissue sections. In newborn mice subjected to experimental models of infections or hypoxia–ischemia; luciferase signal increased in brains of live animals. In brain sections dEGFP expression, revealing NF‐κB activation was observed in the endothelial cells of the blood–brain barrier in all disease models. In meningitis and hypoxia–ischemia expression of dEGFP was also induced in perivascular astrocytes. In conclusion, by using this transgenic reporter mouse in experimental models of perinatal complications, we could assess NF‐κB activity in vivo and subsequently determine the cellular origin in the tissues.